Analisis Risiko Pada Proses Produksi Dengan Menerapkan Metode House of Risk, AHP dan Pendekatan SCOR Pada PT XYZ - Mohammad Bima Ghozali; Hidayat Hidayat; Yanuar Pandu Negoro (G-Tech: Jurnal Teknologi Terapan, 2024)
PT XYZ is a service company engaged in water treatment.This company is experiencingmany problems in the production process and there is no structured mitigation plan. The aim of this research is to determine the risks that are estimated to exist or have already existed and provide mitigation plans. This research applies the SCOR approach for mapping and the House Of Riskmethod for analyzing and providing risk mitigation. After that, risk analysis was carried out in House Of Riskphase 1 which resulted in 35 Risk events & 30 Risk Agents with 5 priority risk results obtained from ARP estimates including A16, A28, A26, A10, A18, while for preventive The actions obtained from the AHP estimation were 8, namely PA1 with a value of 0.26, PA3 with a value of 0.20, PA2 with a value of 0.17, PA4 with a value of 0.13, PA5 with a value of 0.12, PA6 with a value of 0, 08, PA7 with a value of 0.03, PA8 with a value of 0.02.